Effect of Using Internal Steel Plates for Shear Reinforcement on Flexural Behavior of Self-Compacting Concrete Beams - Ibrahim, Amer M.; Khaled, Zeyad S. M.; Abdul Ameer, Iman M. (Al-Nahrain Journal for Engineering Sciences, 2017)
This research was conducted to investigate the effect of using internal steel plates for shear reinforcement on flexural behavior of SCC beams instead of using traditional reinforcement bars (stirrups) and to study the effect of their spacing and thickness on strength. The experimental work included destructive tests on six SCC beams under two-point load. The results showed that the yield loads in all of the beams with steel plates were lower than the reference beam by (5.21%) on average, the deflection at yield load was higher by (13.72%) on average and the ultimate loads were lower by (6.77%) on average except in one beam where it was higher by (0.37%). It was also found that the ultimate deflection in beams with internal shear steel plates was lower by (10.01%) on average except in the aforementioned beam where it was higher by (2.31%). Ductility in all beams with steel plates was lower by (20.08%) on average and the strain before a load of (200kN) was higher in the longitudinal reinforcement and lower in shear steel plates and vice versa after a load of (200kN). Theoretical analysis was also carried out for all beams using the finite element program ANSYS (version 15) where theoretical results of load versus mid-span deflection relations, longitudinal reinforcement strain, shear reinforcement strain, variations of neutral axis depths and cracks patterns showed good agreement with experimental ones. Finally, some specific further studies were recommended.